Challenges and Advances in Electrical and Thermal Modeling of High-Precision PMSM Drives - Azom, Md Ali; Khan, Md. Yakub Ali (Control Systems and Optimization Letters, 2025)
This review examines the challenges and advancements in electrical and thermal modeling of PMSM systems, emphasizing their interdependence and practical applications. Permanent Magnet Synchronous Motors (PMSMs) are essential for high-precision applications including electric vehicles, robots, and aerospace systems because of their exact controllability, high efficiency, and high-power density. However, maximizing PMSM drive performance necessitates a thorough comprehension of both their thermal and electrical properties. The difficulties and developments in electrical and thermal modeling for PMSMs are thoroughly examined in this paper, with a focus on high-precision applications. The research starts by going over the basics of PMSM drives and their operating parameters. Next, it examines important electrical modeling methods, such as finite element methods, dq-axis transformations, and approaches to nonlinearities like saturation and harmonics. The conversation goes on to explore thermal modeling techniques, emphasizing computational fluid dynamics, lumped parameter models, and finite element thermal analysis. The review emphasizes how important integrated electrical-thermal models are for accurately predicting the coupled dynamics of electrical performance and heat generation in high-performance applications. Innovative solutions including machine learning-driven models, hybrid approaches, and the usage of digital twins are considered alongside major problems like computational complexity, parameter identification, and real-time implementation. In addition, this paper looks at real-world case studies that demonstrate how sophisticated modeling approaches can improve PMSM designs and guarantee thermal stability in a range of operating scenarios. The development of real-time simulation techniques, investigation of new cooling materials, and improvements in multi-physics modeling are among the final research directions mentioned. Future directions include advancements in real-time simulation, novel cooling materials, and multi-physics modeling. By highlighting this early integration, the study offers a cohesive framework that improves comprehension of coupled electro-thermal phenomena, setting it apart from traditional research and making it an invaluable tool for engineers and researchers.